Study of Bone Marrow Mesenchymal and Tendon-Derived Stem Cells Transplantation on the Regenerating Effect of Achilles Tendon Ruptures in Rats - Mohanad Kh Al-ani; Kang Xu; Yanjun Sun; Lianhong Pan; ZhiLing Xu; Li Yang (Stem Cells International)
Comparative therapeutic significance of tendon-derived stem cells (TDSCs) and bone marrow mesenchymal stem cells (BMSCs) transplantation to treat ruptured Achilles tendon was studied. Three groups of SD rats comprising 24 rats each, designated as TDSCs and BMSCs, and nontreated were studied for regenerative effects through morpho-histological evaluations and ultimate failure load. For possible mechanism in tendon repair/regeneration through TDSCs and BMSCs, we measured Collagen-I (Col-I), Col-III gene expression level by RT-PCR, and Tenascin-C expression via immunofluorescent assay. TDSCs showed higher agility in tendon healing with better appearance density and well-organized longitudinal fibrous structure, though BMSCs also showed positive effects. Initially the ultimate failure load was considerably higher in TDSCs than other two study groups during the weeks 1 and 2, but at week 4 it attained an average or healthy tendon strength of 30.2 N. Similar higher tendency in Col-I/III gene expression level during weeks 1, 2, and 4 was observed in TDSCs treated group with an upregulation of 1.5-fold and 1.1-fold than the other two study groups. Immunofluorescent assay revealed higher expression of Tenascin-C in TDSCs at week 1, while both TDSCs and BMSCs treated groups showed detectable CM-Dil-labelled cells at week 4. Compared with BMSCs, TDSCs showed higher regenerative potential while treating ruptured Achilles tendons in rats.